Comparison of step-by-step kinematics of resisted, assisted and unloaded 20-m sprint runs - van den Tillaar, R.; Gamble, P. (Sports Biomechanics, 2019)
This investigation examined step-by-step kinematics of sprint running acceleration. Using a randomised counterbalanced approach, 37 female team handball players (age 17.8 ± 1.6 years, body mass 69.6 ± 9.1 kg, height 1.74 ± 0.06 m) performed resisted, assisted and unloaded 20-m sprints within a single session. 20-m sprint times and step velocity, as well as step length, step frequency, contact and flight times of each step were evaluated for each condition with a laser gun and an infrared mat. Almost all measured parameters were altered for each step under the resisted and assisted sprint conditions (n² = 0.28). The exception was step frequency, which did not differ between assisted and normal sprints. Contact time, flight time and step frequency at almost each step were different between `fast` vs. `slow` sub-groups (n² = 0.22). Nevertheless overall both groups responded similarly to the respective sprint conditions. No significant differences in step length were observed between groups for the respective condition. It is possible that continued exposure to assisted sprinting might allow the female team-sports players studied to adapt their coordination to the `over-speed` condition and increase step frequency. It is notable that step-by-step kinematics in these sprints were easy to obtain using relatively inexpensive equipment with possibilities of direct feedback.